Knowledge by way of prophecy - Rabinowitz, D (2013)
This thesis investigates whether beliefs acquired by way of prophecy are safe. By ‘prophecy’ I have in mind the presentation of the prophetic method as found in the Guide of the Perplexed, which was Moses Maimonides’ philosophical masterpiece. And by ‘safe’ I have in mind the work by Timothy Williamson on the safety condition for knowledge. Both authors have proven to be dominant forces on these respective topics. The significance of this investigation derives from the centrality of prophecy to the three monotheistic religions. My main goal in this thesis is to identify those safety risks associated with the prophetic method. In this manner I aim to undermine any presumption in favor of prophetic beliefs as a whole being safe. Importantly, this general conclusion does not entail of a specific prophetic belief p that p is unsafe. Additionally, the scope of these results is restricted to the model of prophecy found in the Guide. The thesis begins with a critical elucidation of Williamson’s extensive work on the safety condition for knowledge. Particular attention is paid to those issues related to method individuation and Williamson’s cumulative conception of bases. Matters concerning these two topics inform the reading of Maimonides on prophecy found in the second chapter. In particular, I argue that Maimonides should be read as defending a cumulative conception of prophecy. As I emphasize several times during the chapter, the epistemology of prophecy cannot be reduced to the epistemology of testimony since prophecy for Maimonides does not involve the transfer of a proposition from God to the prophet. The third chapter is devoted to identifying those elements of the prophetic method that involve room for error. I argue that while all belief-forming methods in a fallibilist epistemology contain room for error, some are riskier than others. Prophecy should be considered one of the riskier sort. The fourth and final chapter shifts attention to non-standard semantics for ‘knows,’ David Lewis’s in particular. I argue that the interaction between such semantics and the laws governing prophecy in Jewish law is problematic. In particular, I demonstrate that such semantics destabilize the prophetic phenomenon. As such, we must either choose invariantism and gain stability, or choose non-standard semantics for ‘knows’ and live with this lack of stability.